PHARMACOLOGICAL AND BIOLOGICAL EVALUATION OF METHANOL EXTRACTS OF SELECTED CHOLISTANI PLANTS - Fatima Sadiq; Hadeeqa Habib; Mirza Imran Shahzad; Kiran Fatima; Haleema Saeed; Maryam Shafiq; Saba Ajmal; Tamawul Noor; Muneeza Mustafa; Hina Ashraf; Irfan Saeed (Journal of Animal and Plant Sciences, 2024)
Cholistani plants are a rich source of bioactive compounds that are helpful in treating various ailments. The objective of the current investigation was to elucidate the pharmacological importance of four Cholistani plants including L. indicum, E. granulata, C. prostratus, and H. crispum. Methanolic extracts of these plants were subjected to antibacterial, antibiofilm, antioxidant, antidiabetic, and antiviral analysis. Disc diffusion assay was used for antibacterial activity and the MIC of active extracts was also calculated. In vitro antibiofilm assay was conducted against drug-resistant and drug-sensitive bacterial strains and % inhibition was calculated. DPPH assay was used for the evaluation of antioxidant potential. The antidiabetic potential was tested by α-glucosidase inhibitory assay. The Haemagglutination (HA) test was performed to assess the antiviral properties of these plants against the Avian Influenza Virus (H9N2). It was found that E. granulata prevailed in antibacterial potential with max ZoI against selected bacterial strains (16.5 mm versus E. coli. C. prostratus) surpassed all other plant extracts in terms of biofilm inhibition with up to 90% inhibition against P. aeruginosa. Considerable antioxidant potential was revealed by all examined plants in the order of E. granulata> C. prostratus > L. indicum > H. crispum. A substantial α-glucosidase inhibitory potential was detected in all the studied plants. All of the examined plants displayed significant (titer 0) antiviral activity. This study reveals that all of these plants have the potential to be employed as antibacterial, antioxidant, and antiviral agents. In vitro suppression of the α-glucosidase enzyme indicated that these plants are potent sources of antidiabetic compounds.In conclusion, all of the examined Cholistani plants are rich sources of pharmacological compounds and should be further researched for drug development.
Keywords: E. granulata; C. prostratus; L. indicum; H. crispum; antibacterial; antioxidant; antibiofilm; antiviral